Fishing Across the Centuries: What Prospects for the Venice Lagoon? - Silvia Silvestri; M. Pellizzato; V. Boatto (Fondazione Eni Enrico Mattei (FEEM), 2006)
Fishing has always been an important activity for those Venetians who live near the Lagoon, and it still enjoys an important economic and social role in the region. Over the last few years, however, the fishing industry has been subject to a profound transformation both in the reduction of the variety and the abundance of the species found in the lagoon, and in the change from a complex and well-structured type of activity to one which has become monospecialist, that is based principally on the fishing of the bivalve Tapes philippinarum (Adam & Reeve). The widespread diffusion of this bivalve and its considerable commercial value have resulted in an increased harvest, initially carried out by hand but now by more sophisticated methods which are capable of obtaining much higher yields. The social, economic and environmental problems resulting from this automated fishing have stimulated research into alternative strategies to manage the alieutic resources of the lagoon which will allow fishing to become a sustainable activity without inflicting long-term environmental damage. This present work will try and prepare the foundations for a system of eco-compatible management, based on an analysis of the functioning of the lagoons eco-system, defined as a paralic model, the observation of the traditional forms of fishing practiced over the centuries, a technical analysis of the present typology of lagoon fishing (fishing with fyke nets, vallicoltura and fishing of fish fry for rearing, clam fishing (Tapes philippinarum), mussel culture) with particular reference to the species fished, the distribution of the activity throughout the year and the technology employed, to the productivity of the various fishing methods.
Keywords: Q22; 330; Venice Lagoon; Fyke nets; Clam Fishing management; Fish Farming